Comparing eco-civilization theory and practice: Big-data evidence from China. (20th December 2022) - Wang, Ning; Guo, Jinling; Zhang, Jian; Fan, Yu
Abstract: Constructing an eco-civilization is crucial in achieving green, low-carbon development, and thus bridging the gap between theory and practice is imperative to better promote urban ecological transformation. At present, there are inconsistencies and imbalances between theoretical research and practical efforts to achieve an eco-civilization. This paper uses bibliometric analysis and Latent Dirichlet Allocation to analyze China's progress towards an eco-civilization at the theoretical and practical levels. The 'theory' is analyzed using 632 articles, while the 'practice' is analyzed using 100 eco-civilization pilot zone reports. The two are compared, with results showing: First: from 2015 onwards, the theory is moving in an interdisciplinary direction, with seven themes focusing on macro topics. Second: eco-civilization construction projects have multiple overlapping themes, and the growing connection between energy consumption, economic growth and environmental impacts driven by significant projects is the key to improving the level of regional ecological development. Third: the theory and practice are similar in that both are concerned with environmental protection, ecological education, and ecotourism. However, eco-civilization construction projects lack forward-looking and dynamic development tracking of low-carbon research. Finally: the paper proposes that dynamic evaluation and project tracking methods should be applied to monitor critical indicators to achieve a solid link between the theory and practice during eco-construction projects. This paper also proposes academia should do more research on townships and other micro level phenomena to promote climate change and energy revolution in the construction of a Chinese eco-civilization. Highlights: Analysis of the similarities and differences between theoretical research and practical measures of eco-civilization. Academic research focuses on sustainability, while practical activities lack attention to climate change. Optimizing the energy-economy-environment integration project is the key to improving China's ecology. Environmental protection, eco-civilization education, and eco-tourism are common concerns in the theory and practice. Suggestions include focusing on crucial indicators and micro-level activities.